Structural and dielectric properties of epitaxial Ba0.6Sr0.4TiO3 thin films grown on Si substrates with thin SrO buffer layers - Kim, Hyun-Suk; Hyun, Tae-Seon; Kim, Ho-Gi; Yun, Tae-Soon; Lee, Jong-Chul; Kim, Il-Doo (SPRINGER, 2007)
(100) epitaxial Ba0.6Sr0.4TiO3 (BST) thin films were grown on Si substrates using a 9 nm thick SrO buffer layer. The phase shifter fabricated on BST films grown on a SrO buffered Si substrate showed a larger figure of merit (FOM) of 24.7 degrees/dB as a result of improving the phase tuning while retaining an appropriate insertion loss compared to that (15.3 degrees/dB) for the BST/MgO structure. This work demonstrates that a thin SrO buffer layer plays an important role in the successful integration of BST-based microwave tunable devices onto Si wafers.
Keywords: MICROWAVE PROPERTIES; HETEROSTRUCTURE; INTEGRATION; TA2O5